Measuring and improving customer satisfaction towards Kampungku Restaurant / Abang Mohammad Zulfiqar Za'im - Za'im, Abang Mohammad Zulfiqar (2011)
The main objectives of this research were to identify attributes that influence customer satisfaction and determine their relationships with customer satisfaction. The variables included in this research are service, physical, product and promotion as independent variables and customer satisfaction as the dependent variable. A set of questionnaire were constructed by measuring demographics factors, independent variables and dependent variables. 52 respondents consisted of customers whom dining at Kampungku Restaurant were selected as a sample. From the findings, there were significant relationship between service attributes (r=0.776**, p=0.001), physical attributes (r=0.760**, p=0.002), product attributes (r=0.747**, p=0.659) and promotion (r=0.744**, p=0.008).. Thus new findings were discovered after conducting this research. Future researchers could concentrate on determining attributes that influence customer satisfaction.